Exploring persuasion knowledge in food advertising: an empirical analysis - Svenja Mohr; Rainer Kühl (SN Business & Economics, 2021)
Food purchase decisions are characterized by habitual purchase behavior and low consumer involvement. The main aim of food marketing is to influence food consumers, for example, through advertising. In order to illustrate the interaction between consumers and marketers, Friestad and Wright (1994) developed the Persuasion Knowledge Model. The Persuasion Knowledge Model postulates that consumers' dealing with persuasion attempts depends on three knowledge factors: persuasion, agent, and topic knowledge. In this paper, we apply the Persuasion Knowledge Model to food advertising. Based on an online survey with German students (n0.167em=0.167em420), a structural equation analysis is used to investigate how persuasion knowledge determinants influence food consumers' avoidance of the persuasion attempt which is presented as a hypothetical but typical food advertisement. Results show that the dependent variable beliefs about consumers' avoidance of the persuasion attempt is negatively influenced by consumers' beliefs about psychological mediators in the advertisement and by consumers' beliefs about the appropriateness and effectiveness of the persuasion tactic. The determinant consumers' beliefs about persuasion coping goals and tactics positively influences consumers' avoidance of the persuasion attempt. From these findings, we derive recommendations for food industry advertisers and consumer education.
Keywords: L66; Q18; D12; 330; Persuasion knowledge; Structural equation model; Survey; Food advertising; Consumer behavior